Kemampuan Literasi Sains Siswa Sekolah Dasar di Sekolah Adiwiyata (Studi Deksriptif di SD Adiwiyata X Kota Padang) - Safrizal Safrizal; Lenny Zaroha; Resti Yulia (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
The aims of this study is to describe the ability of scientific literacy of students in Adiwiyata’s school on three aspects, they are content, context, and attitude. The importance of having scientific literacy is one of the competencies must be possessed in 21st century education. Adiwiyata School is one of the concrete steps of the government to instill the principles and competences of scientific literacy. The research method used is descriptive quantitative. The research sample was taken using simple random sampling technique. The data collection was carried out by distributing questions and questionnaires to students in Adiwiyata School. Then, the data was analyzed using descriptive statistics by referring to categorization norms. The results showed that the scientific literacy ability of elementary school students in Adiwiyata School was in the high category. Furthermore, the ability of scientific literacy aspects of attitudes in Adiwiyata school students is in the high category namely X> 53.6. While the ability of scientific literacy in the aspect of content included in the category is quite low. The acquisition of scientific literacy skills in students at Adiwiyata school is believed to be influenced by the characteristics of the school in internalizing the values of science in teaching and learning activities in the classroom. Keywords: adiwiyata, scientific literacy, content, and contextABSTRAK.Tujuan penelitian ini adalah untuk mendeskripsikan kemampuan literasi sains siswa di sekolah Adiwiyata pada tiga aspek, yakni konten, konteks, dan sikap. Pentingnya memiliki Literasi sains menjadi salah satu kompetensi yang harus dimiliki dalam pendidikan abad 21. Sekolah Adiwiyata menjadi salah satu langkah konkrit pemerintah untuk menanamkan prinsip dan kompetensi literasi sains. Metode penelitian yang digunakan adalah kuantitatif deskriptif. Pengambilan sampel penelitian dilakukan dengan teknik simple random sampling Pengumpulan data dilakukan dengan cara menyebarkan soal dan kuesioner kepada siswa di Sekolah Adiwiyata. Kemudian, data di analisis dengan menggunakan Statistik Deskriptif dengan merujuk pada norma kategorisasi. Hasil penelitian menunjukkan bahwa kemampuan literasi sains siswa sekolah dasar di Sekolah Adiwiyata berada pada kategori tinggi. Selanjutnya, kemampuan literasi sains aspek sikap pada siswa sekolah Adiwiyata berada pada kategori tinggi yakni X > 53,6. Sedangkan kemampuan literasi sains pada aspek konten termasuk dalam kategori cukup rendah. Pemerolehan kemampuan literasi sains pada siswa di sekolah Adiwiyata diyakini dipengaruhi oleh ke-khas-an sekolah dalam menginternalisasi nilai-nilai sains dalam aktivitas belajar mengajar di kelas.Kata kunci: adiwiyata, literasi sains, konten, konteks, sikap